The Effect Of Management Styles On Learning Organization Practices In The Private (Multinational/Local) Companies. - Abdullah., Mirza Manirajah (2000)
This research attempts to examine the type of management styles that cultivate the learning organization practices in the private sector companies. The problem being investigate here involves two major related issues.